Funny and Educational across Cultures: Subtitling Winnie The Pooh into Italian - Adriana Tortoriello (JoSTrans: The Journal of Specialised Translation)
Subtitling a children's programme, especially a cartoon or animated programme, presents the subtitler with specific constraints and challenges. These are due, on a lexico-semantic and visual level, to the nature of the source language text, and on a pragmatic level, to that of the prospective audience. Through the analysis of some examples taken from the Italian subtitled version of the series The Book of Pooh, this article seeks to consider in greater detail both the issues involved and the strategies the translator has put in place in order to deal with such a unique situation.